M1 and M2 Monocytes in Rheumatoid Arthritis: A Contribution of Imbalance of M1/M2 Monocytes to Osteoclastogenesis - Fukui, Shoichi; Iwamoto, Naoki; Takatani, Ayuko; Igawa, Takashi; Shimizu, Toshimasa; Umeda, Masataka; Nishino, Ayako; Horai, Yoshiro; Hirai, Yasuko; Koga, Tomohiro; Kawashiri, Shin-ya; Tamai, Mami; et al. (Frontiers in Immunology, 2018)
Objectives: We investigated the relationships among M1 monocytes, M2 monocytes, osteoclast differentiation ability and clinical characteristics in patients with rheumatoid arthritis (RA). Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from RA patients and healthy donors, and we then investigated the number of M1 monocytes or M2 monocytes by fluorescence-activated cell sorting. We also obtained and cultured CD14-positive cells from PBMCs from RA patients and healthy donors to investigate osteoclast differentiation in vitro. Results: Forty RA patients and 20 healthy donors were included. Twenty-two patients (55%) were ACPA-positive. The median M1/M2 ratio was 0.59 (0.31–1.11, IQR). There were no significant differences between the RA patients and healthy donors. There was a positive correlation between the M1/M2 ratio and the differentiated osteoclast number in vitro in RA patients (ρ=0.81, p<0.001). The ACPA-positive patients had significantly higher M1/M2 ratios in vivo (p=0.028) and significantly greater numbers of osteoclasts in vitro (p=0.005) than the ACPA-negative patients. Multivariable regression analysis revealed that the M1/M2 ratio was the sole significant contribution factor to in vitro osteoclastogenesis. RA patients with M1/M2 ratios >1 (having relatively more M1 monocytes) had higher C-reactive protein and erythrocyte sedimentation rates than RA patients with M1/M2 ratios ≤1. M1-dominant monocytes in vitro produced higher concentrations of IL-6 upon stimulation with lipopolysaccharide than M2 monocytes. Conclusion: M1/M2 monocytes imbalance strongly contributes to osteoclastogenesis of RA patients. Our findings cast M1 and M2 monocyte subsets in a new light as a new target of treatments for RA to prevent progression of osteoclastic bone destruction.